All-solid-state carbon fluoride lithium battery and preparation method thereof
Through the internal series of all-solid carbon fluoride lithium battery structure and the use of sulfide solid electrolyte, the problems of thermal runaway and output voltage limit of lithium fluoride batteries are solved, and the battery performance of high voltage and high energy density is achieved.
Patent Information
- Application Number
- CN202111172599.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2041-10-08
AI Technical Summary
Existing lithium-fluorinated carbon batteries are prone to thermal runaway when used in groups, and the stable voltage of traditional liquid electrolytes limits the output voltage of the single cell.
The all-solid carbon fluoride lithium battery structure is adopted in series, and the laminates are repeatedly connected in series through multiple battery cells, using sulfide solid electrolyte and carbon fluoride material, combined with aluminum-plastic film packaging and isostatic hot pressing treatment.
The working voltage of the single cell is improved, the high-temperature performance and safety of the battery is enhanced, the mass proportion of non-fluorinated carbon components is reduced, and the energy density of the cell is improved.
Smart Images

Figure CN113921820B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of all-solid-state lithium primary batteries, and in particular relates to a high-specific-energy and high-voltage carbon fluoride solid-state lithium battery and a preparation method thereof. Background Art
[0002] In many fields, batteries are the preferred source of power. Lithium primary batteries are the preferred battery system in both civilian and military fields due to their high energy density and long storage life. For example, batteries in electronic cigarettes and batteries for some underwater weapons all use lithium primary batteries. In lithium primary battery systems, lithium carbon fluoride batteries have the highest theoretical specific energy. The theoretical specific capacity of carbon fluoride materials can reach 864 mAh / g, and the theoretical specific energy is 2680 Wh / kg. In actual use, the energy density of carbon fluoride batteries has reached about 800Wh / kg, but carbon fluoride batteries generate a lot of heat and are prone to thermal runaway when used in groups. Therefore, the group application of carbon fluoride batteries is generally discharged at a low rate (≤0.1 C). When too much heat accumulates, accidents such as flatulence and fire will occur. At the same time, due to the limitation of the stable voltage of traditional liquid electrolytes, the output voltage of lithium carbon fluoride monomer cells is below 3 V.
[0003] Compared with traditional lithium-ion batteries, all-solid-state batteries have the advantages of better safety, better energy density and better temperature adaptability (especially high temperature). The ionic conductivity of some high-ionic conductivity sulfide solid electrolytes at room temperature has reached or even exceeded the level of liquid organic electrolytes (10 -2 Scm -1 ), and at high temperatures, the conductivity of sulfide solid electrolytes can be greatly improved, thus exceeding that of liquid electrolytes. At the same time, they are relatively stable at higher temperatures (<120°C) and will not produce boiling and decomposition like organic electrolytes. Therefore, they have incomparable advantages over traditional electrolytes in battery systems such as carbon fluoride that generate a large amount of heat.
[0004] Since solid electrolytes are not fluid, the electrodes can be stacked in series to allow the output voltage of a single cell to exceed 5 V. This has application value in some special scenarios when small-capacity and high-voltage output is required.
[0005] The traditional external series all-solid-state lithium battery structure is as follows Figure 1 As shown, there are problems such as high heat generation of the battery during use, and high heat generation after being grouped, resulting in poor safety. Summary of the invention
[0006] In view of the above defects or improvement needs of the prior art, one of the objects of the present invention is to provide an internally series-connected all-solid-state carbon fluoride lithium battery to solve the problems existing in the prior art.
[0007] The technical solution adopted by the present invention to solve the technical problem is: an all-solid-state carbon fluoride lithium battery, which is composed of a plurality of battery units repeatedly stacked in series; each battery unit is composed of a current collector, a composite positive electrode layer coated on one side of the current collector, a solid electrolyte layer coated or hot-pressed on the surface of the composite positive electrode layer, a negative electrode covered on the surface of the solid electrolyte layer, and a current collector covered on the other side of the negative electrode; the composite positive electrode layer is composed of a positive electrode and a sulfide solid electrolyte for conducting ions, which is composed of 60% to 90% of carbon fluoride, 2% to 5% of a conductive agent, 2% to 5% of a binder, and 5% to 35% of a sulfide solid electrolyte with high ionic conductivity; the negative electrode is a metal lithium negative electrode or a lithium-indium alloy negative electrode; the current collectors at both ends are led out of the positive and negative electrode ears and are packaged as a whole with an aluminum-plastic film.
[0008] The current collector of the all-solid-state carbon fluoride lithium battery is a copper foil or stainless steel foil with a thickness of 2um to 12um. Preferably, the current collector is a copper foil with a thickness of 4.5um.
[0009] The all-solid-state carbon fluoride lithium battery, wherein the carbon fluoride is one or more of graphite fluoride, carbon fiber fluoride, and carbon nanotube fluoride.
[0010] The conductive agent of the all-solid-state carbon fluoride lithium battery is one or more of carbon black, Ketjen black, acetylene black, carbon nanotubes and carbon fibers.
[0011] The binder of the all-solid-state carbon fluoride lithium battery is styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber or polyethylene-vinyl acetate.
[0012] The all-solid-state carbon fluoride lithium battery has a sulfide solid electrolyte selected from the group consisting of an LGPS-type sulfide solid electrolyte, an Argyrodite-type sulfide solid electrolyte, and a glass-ceramic sulfide solid electrolyte; and is prepared by powder cold pressing or coating.
[0013] In the all-solid-state carbon fluoride lithium battery, when the sulfide solid electrolyte is prepared by a coating method, the binder used is SBR (styrene-butadiene rubber), NBR (nitrile-butadiene rubber), HNBR (hydrogenated nitrile-butadiene rubber) or PEVA (polyethylene-vinyl acetate).
[0014] The all-solid-state carbon fluoride lithium battery uses xylene, p-xylene or n-heptane as a solvent when combining the composite positive electrode layer and the solid electrolyte layer by a coating method, and uses SBR (styrene-butadiene rubber), NBR (nitrile rubber), HNBR (hydrogenated nitrile rubber) or PEVA (polyethylene-vinyl acetate) as a binder.
[0015] The second object of the present invention is to provide a method for preparing the above-mentioned all-solid-state carbon fluoride lithium battery, the steps are:
[0016] (1) Carbon fluoride, solid electrolyte and conductive agent are uniformly mixed according to a ratio, and then added to a solution containing a binder, and the carbon fluoride is coated on the current collector by a coating method, and dried at 60-80° C. under vacuum for more than 12 hours for use;
[0017] (2) A layer of sulfide solid electrolyte with a thickness of about 20um to 100um is applied to the carbon fluoride by cold pressing or coating to obtain a composite positive electrode layer;
[0018] (3) After the composite positive electrode layer is dried, a layer of solid electrolyte is coated or hot-pressed on the positive electrode as a solid electrolyte layer, and then a layer of negative electrode is covered to obtain a battery unit;
[0019] (4) Repeating steps (1) to (3) to obtain multiple battery cells, and repeatedly stacking the battery cells to obtain an all-solid-state battery cluster;
[0020] (5) After the positive and negative electrodes are led out with the tabs, they are packaged with aluminum-plastic film. After packaging, they are successively treated with isostatic pressing and hot pressing. The pressure is 10 to 30 MPa and the hot pressing temperature is 80 to 120 °C.
[0021] In general, compared with the prior art, the above technical solution can achieve the following beneficial effects:
[0022] (1) The internal series connection method adopted by the present invention can connect the pole pieces in the single cell in series using solid electrolytes, which can increase the working voltage of the single cell by several times or even dozens of times to cope with special batteries required in some special scenarios;
[0023] (2) The internal series connection method adopted by the present invention can save some non-fluorinated carbons such as aluminum plastic film when preparing large-capacity batteries, which is different from the external series connection method of traditional lithium batteries, thereby improving the battery specific energy;
[0024] (3) The present invention uses a sulfide solid electrolyte to solve the problems of high heat generation, poor heat dissipation and safety during group discharge in the existing carbon fluoride battery system. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of a traditional external series all-solid-state lithium battery;
[0026] Figure 2 This is a schematic diagram of the structure of the all-solid-state carbon fluoride lithium battery connected in series internally in the present invention;
[0027] Figure 3 It is a schematic diagram of the internal composition of the present invention;
[0028] Figure 4 The battery structure in Example 2 of the present invention;
[0029] Figure 5 The discharge temperature rise curves of Example 2 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The "internal series connection" of the present invention is achieved by directly connecting each group of positive and negative electrodes in series. Compared with traditional lithium batteries, the electrodes inside the single cell are all connected in parallel because the fluid electrolyte cannot withstand a voltage above 5V. Solid electrolytes do not flow and do not have this problem.
[0032] In the preparation of the composite positive electrode layer, uniform mixing is very important. Uneven mixing will affect the performance and capacity of the battery. The uniform mixing method can be drum mixing, which is performed at a low speed in a dedicated mixing equipment to avoid damaging the structure of the electrolyte.
[0033] After packaging, the battery needs to be subjected to isostatic pressing and 100°C hot pressing treatment to ensure contact within the entire solid-state battery and reduce interface impedance.
[0034] Example 1
[0035] like Figure 2 and Figure 3 As shown, the present invention discloses an all-solid-state carbon fluoride lithium battery, which is composed of a plurality of battery units repeatedly stacked in series; each battery unit is composed of a current collector, a composite positive electrode layer coated on one side of the current collector, a (pure) solid electrolyte layer coated or hot-pressed on the surface of the composite positive electrode layer, a negative electrode covered on the surface of the solid electrolyte layer, and a current collector covered on the other side of the negative electrode; the composite positive electrode layer is composed of a positive electrode and a sulfide solid electrolyte for conducting ions and replacing a traditional lithium battery separator, and is composed of 60% to 90% carbon fluoride, 2% to 5% conductive agent, 2% to 5% binder, and 5% to 35% sulfide solid electrolyte with high ionic conductivity. The preferred carbon fluoride, sulfide solid electrolyte, conductive agent, and binder (solvent) are: graphite fluoride: Li 10 GeP2S 12, carbon nanotubes, hydrogenated nitrile rubber (xylene) = 75:15:6:4; the solid electrolyte layer and the sulfide solid electrolyte are the same solid electrolyte, the negative electrode is a metal lithium negative electrode or a lithium indium alloy negative electrode, and the preferred metal negative electrode is a metal lithium negative electrode; the current collectors at both ends lead out the positive and negative electrode ears and are packaged as a whole with an aluminum-plastic film.
[0036] Among them, the current collector is a copper foil or stainless steel foil with a thickness of 2um to 12um, and the preferred current collector is a copper foil with a thickness of 4.5um; the carbon fluoride is one or more of fluorinated graphite, fluorinated carbon fiber, and fluorinated carbon nanotubes; the conductive agent is one or more of carbon black, Ketjen black, acetylene black, carbon nanotubes, and carbon fibers; the binder is styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber, or polyethylene-vinyl acetate; the sulfide solid electrolyte is one or more of LGPS-type sulfide solid electrolyte, Argyrodite-type sulfide solid electrolyte, and glass-ceramic sulfide solid electrolyte, and the preparation method is powder cold pressing or coating.
[0037] When the sulfide solid electrolyte is prepared by a coating method, the binder used is SBR (styrene butadiene rubber), NBR (nitrile rubber), HNBR (hydrogenated nitrile rubber) or PEVA (polyethylene vinyl acetate); when the composite positive electrode layer and the solid electrolyte layer are combined by a coating method, xylene, p-xylene or n-heptane is used as a solvent, and SBR (styrene butadiene rubber), NBR (nitrile rubber), HNBR (hydrogenated nitrile rubber) or PEVA (polyethylene vinyl acetate) is used as a binder. The preferred solvent and binder are xylene and HNBR (hydrogenated nitrile rubber), respectively, and the ratio of the solvent and the binder is adjusted according to the specific viscosity.
[0038] The preparation method of the above-mentioned all-solid-state carbon fluoride lithium battery comprises the following steps:
[0039] (1) Carbon fluoride, solid electrolyte and conductive agent are uniformly mixed according to a ratio, and then added to a solution containing a binder, and the carbon fluoride is coated on the current collector by a coating method, and dried at 60-80° C. under vacuum for more than 12 hours for use;
[0040] (2) A layer of sulfide solid electrolyte with a thickness of about 20um to 100um is applied to the carbon fluoride by cold pressing or coating to obtain a composite positive electrode layer;
[0041] (3) After the composite positive electrode layer is dried, a layer of solid electrolyte is coated or hot-pressed on the positive electrode as a (pure) solid electrolyte layer (replacing the separator and conductive ions of traditional lithium batteries, and the coating method requires corresponding binders and solvents), and then a layer of negative electrode is covered to obtain a battery cell;
[0042] (4) Repeating steps (1) to (3) to obtain multiple battery cells, and repeatedly stacking the battery cells to obtain an all-solid-state battery cluster;
[0043] (5) After the positive and negative electrodes are led out with the tabs, they are packaged with aluminum-plastic film. After packaging, they are successively treated with isostatic pressing and hot pressing. The pressure is 10 to 30 MPa and the hot pressing temperature is 80 to 120 °C.
[0044] The present invention obtains high voltage through internal series connection, which is suitable for special scenarios that require a higher output voltage. Compared with external series connection, the mass proportion of components such as aluminum-plastic film can be reduced, and the energy density of the battery cell can be improved. At the same time, the solid-state battery system is well matched to the high calorific value of carbon fluoride, so that the high temperature performance and safety performance of the battery are improved.
[0045] Example 2
[0046] A 2Ah solid-state battery cell with a voltage platform of 25V was prepared. There were 10 groups of positive and negative electrodes connected in series inside the battery cell. Each group of electrodes provided a voltage of 2.5V and a capacity of 2Ah.
[0047] like Figure 4 As shown, the internal series solid-state carbon fluoride battery of Example 2 comprises: a current collector, a composite positive electrode layer coated on one side of the current collector, a (pure) solid electrolyte layer coated or hot-pressed on the surface of the composite positive electrode layer, a metal negative electrode covered on the surface of the (pure) solid electrolyte, and a current collector covered on the other side of the metal negative electrode; the above series units are repeatedly stacked to form a cluster of internal series batteries, and the number of repetitions is 10. The positive and negative tabs are respectively led out on both sides of the cluster, and the entire cluster is encapsulated with an aluminum-plastic film.
[0048] The internal series connection and all-solid-state components used in the present invention can enable the battery cell to output a voltage 10 times that of an ordinary battery cell. Currently, the internal parts of commercial lithium battery cells are stacked in parallel, and the voltage is the same as that of the single-chip positive and negative electrodes, which is about 2.5 to 4.5V. The corresponding carbon fluoride battery system is about 2.5V. When traditional battery cells using electrolytes are connected in series internally, the electrolyte will pass through the entire battery cell due to its fluidity, and therefore cannot withstand the high voltage caused by the series connection. Therefore, traditional battery cells need to obtain high voltage through external series connection.
[0049] The composite positive electrode layer material of the battery is carbon fluoride, the electrolyte is Li6PS5Cl, the conductive agent is Ketjen black and carbon nanotubes, and the binder is hydrogenated nitrile rubber. The current collector is copper foil, and the negative electrode is metallic lithium. The specific preparation steps are as follows:
[0050] (1) In a dry air environment, graphite fluoride, solid electrolyte Li6PS5Cl, Ketjen black and carbon nanotubes are uniformly mixed in a mass ratio of 70:20:5:5, and then the mixed powder is added to a xylene solution containing hydrogenated nitrile rubber and stirred evenly. The mass ratio of hydrogenated nitrile rubber to powder is 5:95, and the mass ratio of hydrogenated nitrile rubber to xylene is 20:100.
[0051] (2) The slurry obtained by stirring is coated on a 4.5 μm thick copper foil by a blade coating method to a thickness of 200 μm, and then dried in a vacuum drying oven at 100°C for later use.
[0052] (3) A layer of sulfide solid electrolyte is applied on the dried positive electrode plate by a doctor blade method. The solid electrolyte slurry Li6PS5Cl, solvent (xylene), and binder (hydrogenated nitrile rubber) are uniformly stirred, and the mass ratio is Li6PS5Cl: xylene: hydrogenated nitrile rubber = 90:300:5. After coating, it is placed in a vacuum drying oven at 100°C for drying, and the thickness of the obtained electrolyte layer is about 10um.
[0053] (4) Slice the composite positive electrode layer and electrolyte, take 10 such electrode sheets, cover the exposed side of the copper foil with a slightly smaller layer of metal lithium negative electrode, and repeatedly stack the structure to obtain an all-solid-state battery cluster.
[0054] (5) After the positive and negative electrodes are welded and led out with the pole ears, they are packaged with aluminum-plastic film. After packaging, isostatic pressing and 100°C hot pressing are used successively.
[0055] The discharge temperature diagram of the internal series fluorinated carbon all-solid-state battery prepared in Example 2 is as follows Figure 5 As shown, the discharge temperature rise of the battery is about 27 degrees.
[0056] The advantages of adopting this technical solution are reflected in the following aspects: sulfide solid electrolytes are matched with battery systems such as carbon fluoride, which have a high heat generation, so that the battery has higher reliability and electrical performance at high temperatures. Since sulfide solid electrolytes exhibit higher ionic conductivity at high temperatures, the internal resistance of the battery cell is reduced, resulting in reduced heat generation, and solid-state batteries also have almost no risk of combustion. At the same time, since solid electrolytes are not fluid, the pole pieces can be directly stacked in series, so that the output voltage of the single cell exceeds 5 V, which has application value in some special scenarios when small capacity and high voltage output are required.
[0057] Comparative Example 1
[0058] The comparison is a traditional liquid organic carbon fluoride battery, which consists of a positive electrode, a lithium negative electrode, a separator, an electrolyte and packaging materials. The battery is also composed of 10 groups of 2Ah electrodes in parallel, so the rated voltage of the battery is 2.5V and the capacity is 20Ah:
[0059] (1) In a dry air environment, mix graphite fluoride and conductive carbon evenly, then add the mixed powder into the NMP solution containing PVDF and stir evenly. The mass ratio of graphite fluoride: conductive carbon: PVDF is 90:5:5.
[0060] (2) The slurry obtained by stirring is coated mechanically on a 12 μm thick aluminum foil to a thickness of 200 μm, and then dried in a vacuum drying oven at 100°C for later use.
[0061] (3) The dried positive electrode slices are sliced and assembled with a separator and a metal lithium negative electrode into a battery cell cluster, and 10 groups of positive and negative electrodes are stacked in parallel.
[0062] (4) The positive and negative electrodes are welded and led out using the tabs, and then packaged with aluminum-plastic film.
[0063] Comparative Example 1 is a traditional lithium fluoride carbon battery, and its discharge temperature rise curve is as follows: Figure 5 As shown, the discharge temperature rise is about 30 o C or so.
[0064] In summary, the present invention utilizes the high ionic conductivity, good thermal stability, and non-flowability of solid electrolytes at high temperatures to prepare an internally series-connected solid-state carbon fluoride battery. The sulfide solid electrolyte, which is stable at high temperatures and has high ionic conductivity, is well matched to the high heating characteristics of carbon fluoride, thereby improving the reliability of the battery. At the same time, the internal series structure provides a solution for optimizing the battery structure and improving the energy density of the battery cell, and the single high-voltage battery cell can be used in some special environments that require high output voltage and low capacity.
[0065] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an all-solid-state carbon fluoride lithium battery, characterized in that: The all-solid-state carbon fluoride lithium battery is composed of multiple battery units repeatedly stacked in series; each battery unit is composed of a current collector, a composite positive electrode layer coated on one side of the current collector, a solid electrolyte layer coated or hot-pressed on the surface of the composite positive electrode layer, a negative electrode covered on the surface of the solid electrolyte layer, and a current collector covered on the other side of the negative electrode; the composite positive electrode layer is composed of 60% to 90% carbon fluoride, 2% to 5% conductive agent, 2% to 5% binder and 5% to 35% sulfide solid electrolyte; the carbon fluoride is one or more of fluorinated graphite, fluorinated carbon fiber, and fluorinated carbon nanotubes, the conductive agent is one or two of Ketjen black and acetylene black, and the binder is styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber or polyethylene-vinyl acetate. The sulfide solid electrolyte is one or both of LGPS type sulfide solid electrolyte and Argyrodite type sulfide solid electrolyte, and the preparation method is coating. When the sulfide solid electrolyte is prepared by coating, the binder used is styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber or polyethylene-vinyl acetate. When the composite positive electrode layer and the solid electrolyte layer are combined by coating, xylene, p-xylene or n-heptane is used as a solvent, and styrene-butadiene rubber, nitrile rubber, hydrogenated nitrile rubber or polyethylene-vinyl acetate is used as a binder; the negative electrode is a lithium-indium alloy negative electrode; the current collector is a copper foil or stainless steel foil with a thickness of 2um to 12um, and the current collectors at both ends are led out of the positive and negative electrode ears and are packaged as a whole with an aluminum-plastic film; the following steps are included: (1) Coating the carbon fluoride on the current collector by a coating method, and drying at 60-80°C under vacuum for more than 12 hours; (2) coating a layer of sulfide solid electrolyte with a thickness of 20 um to 100 um on the carbon fluoride by a coating method to obtain a composite positive electrode layer; (3) After the composite positive electrode layer is dried, a layer of solid electrolyte is coated or hot-pressed as a solid electrolyte layer, and then a layer of negative electrode is covered to obtain a battery unit; (4) Repeating steps (1) to (3) to obtain multiple battery cells, and repeatedly stacking the battery cells to obtain an all-solid-state battery cluster; (5) After the positive and negative electrodes are led out with the tabs, they are packaged with aluminum-plastic film. After packaging, they are successively treated with isostatic pressing and hot pressing. The pressure is 10 to 30 MPa and the hot pressing temperature is 80 to 120°C.
Citation Information
Patent Citations
Internal series type battery cell and internal series type battery
CN110635175A
All-solid state lithium carbon monofluoride batteries
US20150295241A1